Characterization of MoSe2 thin film deposited at room temperature from solution phase - Hankare, P. P.; Patil, A. A.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Manikshete, A. H.; Mulla, Imtiaz S. (Journal of Crystal Growth, 2008)
A simple, low-temperature method has been developed to synthesis molybdenum diselenide semiconductor thin films, based on the chemical reaction of conlplexed ammonium molybdate, hydrazine hydrate and sodium Selenosulphate in aqueous alkaline medium. The deposition parameter of the MoSe2 thin film is interpreted in the present investigation. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), optical absorption and electrical measurements. The deposited film was found to be polycrystalline in hexagonal form. The direct band gap `E-g' for the film was found to be 1.43eV and electrical conductivity in the order of 10(-2)(Omega cm)(-1) with n-type conduction mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Crystal morphology; Growth from solution; Inorganic compound; Polycrystalline deposition; Semiconducting materials; X-ray diffraction

Chemical deposition of CuInSe2 thin films by photoelectrochemical applications - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2012)
Copper indium diselenide films have been synthesized by chemical bath deposition method. The configuration of fabricated cell is n-CuInSe2|NaOH (1 M) + S (1 M) + Na2S (1 M)|C-(graphite). The photoelectrochemical cell characterization of the films is carried out by studying current-voltage characteristics in dark, capacitance-voltage in dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that CuInSe2 thin films are n-type conductivity. The junction ideality factor is found to be 3.81. The flat band potential is found to be 0.763 V. The barrier height value is found to be 0.232 eV. The study of power output characteristic shows open circuit voltage, short circuit current, fill factor and efficiency are found to be 310 mV, 20 mu A, 42.12% and 0.82%, respectively. Photoresponse shows lighted ideality factor which is 2.92. Spectral response shows the maximum current observed at 650 nm. (C) 2011 Published by Elsevier B.V.
Keywords: Chemical bath deposition; Flat band potential; Photo response; Power output; Spectral response